PREHOSPITAL TOURNIQUET USE IN KOCHI PREFECTURE - KOMATSUBARA, Tadashi; MATSUMOTO, Toshiyuki; OKUDA, Ryuichiro; YAMAKAWA, Yasuaki (Journal of the Japanese Association for the Surgery of Trauma, 2024)
ObjectiveTo investigate the effectiveness and problems of prehospital tourniquet use in our hospital.MethodsThos was a single-center retrospective study. Subjects were trauma patients with an Injury Severity Score (ISS) of 9 or higher who were transported to our hospital between 2019 and 2022.ResultsA total of 853 trauma patients were included in this study. There were 194 upper- and 459 lower-extremity trauma cases. Five patients had a tourniquet applied, their median age was 57 years (range, 43 - 83 years), all were male, and they involved two upper- and three lower-extremity trauma cases. One of the five cases had arterial injury (peroneal artery injury). Complications caused by tourniquet use included deep vein thrombosis in one patient and insufficient pressure that contributed to venous hemorrhage in another patient.ConclusionWhile tourniquet use was effective, there were some associated complications. The duration of tourniquet use exceeded two hours in some cases, and this is an issue that needs to be improved.